Розвиток мережі парафій Римо-католицької церкви у Херсонській губернії в ХІХ столітті - Баковецька, Ольга Олександрівна; Bakovetska, Olga O. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
В статті визначено ключові етапи становлення римо-католицької церкви в Херсонській губернії у ХІХ столітті. Проаналізовано внесок окремих осіб в розвиток костьолів. Джерельна база даної роботи базується на архівних матеріалах Державного архіву Саратовської області (Росія) і раніше не використовувалась українськими дослідниками. The main objective of the study is to try, with the help of archival documents that have not previously been used by Russian historians highlight the history of formation and development of the Roman Catholic Church in Kherson province in the XIX century. The article analyzes the circumstances of the appearance of the Roman Catholic community in the region defined administrative affiliation of the Catholic Church in Kherson province, as well as peculiarities of the Roman Catholic Church in a certain area as a whole. This Article analyses the contribution made by certain persons to formation and development of the Roman Catholic church. Attention is paid to the history of the construction of local churches. Identify the key stages in the development of the Roman Catholic Church province and quantitative composition of Catholics living in the area. Source base of this work is based on the archives of the State archive of the Saratov region (Russia), the Russian State historical archive (St.-Petersburg), national historical archives of Belarus (Minsk) and previously used by Ukrainian historians. This provided an opportunity for the author to introduce a scientific revolution is a new array of factual material on the history of the Roman Catholic Church in the southern regions of Ukraine.
Developing a network of parishes of the Roman Catholic Church in the province of Kherson in the XIX century
Keywords: Тираспільська дієцезія; Херсонська губернія; єпископ; візитатор; настоятель; колоністи; Tyraspilska diocese; of Kherson province; Bishop; Visitor; rector; the colonists